Kinetika pelarutan silika amorf dari lumpur panas bumi Dieng - Nurdin Riyanto; P. Sumardi; Indra Perdana (Jurnal Rekayasa Proses, 2012)
Dieng’s geothermal power plant generates not only energy but also wastes as sludge that contains around 50% silica in an amorphous state. The waste has a great potential to be used as a source of micro-amorphous silica synthesis to fulfill industrial needs. This research aimed to study the dissolution kinetics of amorphous silica. In the present work, the alkali – solubilization process by means of the dissolution of amorphous silica in an agitated flask was studied by varying process temperatures (50 – 90 °C), stirring speed (150 – 450 rpm), Na/Si molar ratio (2 – 3), and silica particle size (0,0069 – 0,01975 cm). Experimental results showed that the rate of geothermal silica dissolution increased with temperature and stirring speed. Meanwhile, Na/Si molar ratios and silica particle sizes showed no significant influence on the dissolution process. Calculation results indicated that the dissolution process involved a solid – liquid reaction that occured at the solid surface.